MANAGEMENT OF DIGITAL-BASED MARKETING STRATEGY IN INCREASING THE QUANTITY OF UMRAH PILGRIMS OF PT ARUDAM 99 PROBOLINGGO BRANCH - Zainur Ridho; Muhammad Jalaluddin Assayuthy (Al-Idarah, 2025)
The purpose of this research is to examine the digital marketing strategies used by PT. Arudam 99 Cabang Probolinggo to increase the quantity of umrah participants. The approach used in this research methodology is descriptive qualitative, with the title "Digital-Based Marketing Strategies in Increasing the Quantity of Umrah Participants at PT. Arudam 99 Cabang Probolinggo." This study aims to gather information about the digital marketing strategies implemented at PT. Arudam 99 Cabang Probolinggo. Since this research employs a qualitative approach and includes direct observation, the results are presented in an analytical-descriptive manner, consisting of written words from the responses of individuals observed, particularly regarding the digital-based marketing strategies aimed at increasing the quantity of umrah participants at PT. Arudam 99 Cabang Probolinggo. The research findings indicate that PT. Arudam 99 Cabang Probolinggo has effectively implemented digital marketing in its umrah promotions, especially on social media platforms like Facebook. However, there are shortcomings in its Instagram and website presence.